The performance enhancement of HTM-free ZnO nanowire-based perovskite solar cells via low-temperature TiCl4 treatment. (August 2018) - Islavath, Nanaji; Lingamallu, Giribabu
Graphical abstract: Aligned ZnO nanowire arrays grown on the seeded FTO glass substrate by hydrothermal method. To prepared TiO2 layered ZnO nanowire, nanowires grown substrate immersed in TiCl4 treatment at 3 °C for 30 min, in the refrigerator. TiO2 layer is confirmed by electron microscopy. TiO2 layered ZnO nanowire as charge carrier transport layer combines the advantages of high electron extraction and low interfacial recombination, benefiting electron transport and avoiding charge accumulation. Highlights: ZnO nanowires coated on TiO2 layer by low-temperature hydrolysis for perovskite solar cells. Layers offer the large specific-surface area, higher infiltration. It offers energy barrier for perovskite, drop the dark current and increase the open-circuit voltage. Abstract: Charge carrier transport layer made of aligned ZnO nanowires (NW) coated with TiO2 layer via low-temperature hydrolysis process for perovskite solar cells (PSC) applications. Aligned ZnO NWs were grown by solution approach onto transparent conducting oxide substrates and treated with 25 mM of titanium tetrachloride (TiCl4 ). TiO2 layered ZnO NWs were composed of single crystalline, uniformly covered with amorphous TiO2 nanoparticles was characterized by scanning and transmission electron microscopy. Such TiO2 layered ZnO NW architecture, with the unique combination of high surface-area and infiltration of perovskite more into the electrode and a maximum photocurrent density (JSC ) of 14.30 mA cm −2 and a power conversion efficiency (η) of 7.05% are demonstrated, which is higher than the ZnO NWs. Dark current density is decreased for TiO2 layered ZnO NW-based PSCs, due to the good interface formation between the electrode/sensitizer and it has higher energy barrier to overcome required high onset potential. TiO2 layered ZnO NWs architecture opens up a novel configuration for high-performance optoelectronic devices.